SINERGISITAS STAKEHOLDER DALAM PENGEMBANGAN DESA WISATA PUJON KIDUL KABUPATEN MALANG - Ika Rizkyah Khomzi; Setiyo Yuli Handono; Anis Trianawati (AGRIBUSINESS JOURNAL, 2019)
This study aimed to describe the synergy of stakeholders in development of Pujon Kidul village tourism and the impact from the synergy of stakeholder. This study used qualitative approach and the analysis data used interactif model from Miles and Huberman. Determination of informants was using purposive sampling with consideration of representatives from each stakeholders involved in the development of Pujon Kidul village tourism. The result showed that the level of synergy was in respectful level. The supporting factors in the synergy of stakeholders were openness, mutual benefits, good communications, and no personal interest. Inhibiting factors in the synergy of stakeholders were community perception about Cafe Sawah was different, lacking communication with BNI Brawijaya, lacking knowledge about regulation to develop Cafe Sawah, and mindset money oriented. The results also reveal the impact of the synergy of stakeholder in development Pujon Kidul village tourism especially in Cafe Sawah were employment, encouraging entrepreneurial activity, improve income, increased awareness about cleanliness, decreased of juvenile delinquency, local cultures began to disappear, increased cleanliness, disruptions of traffic around village, and agricultural land conversions.